Revealing the Impact and Meaning of Identity Reproduction in Pasek Community of Hindus in Mataram City, West Nusa Tenggara, Indonesia - Wirawan, I Wayan Ardhi (International Research Journal of Management, IT & Social Sciences, 2017)
Contemporarily identity reproduction at Pasek clanâs ancestors of Hindus in Mataram resulting a number of impacts such as Hindus unification based on genealogical similarity, strengthening militancy based on primordial bond called soroh, Hindus polarization, conflict in Hindu religious practice, genealogic identity reification, development of critical force, deconstruction of established religious practices, orthopraxy of religious practices, empowering member of the clan, entrance of politic and power into religious practice, priesthood status transformation, opening the opportunity to reproduce symbolic power, and developing economic capital power.Â